Pengaruh Anonimitas di Media Sosial terhadap Kebebasan Berpendapat dan Tanggung Jawab Hukum Studi Kasus: (Analisis Kasus Akun Fufufafa dalam Penyebaran Informasi Palsu dan Ujaran Kebencian di Media Sosial Twitter) : Penelitian - Simamora, Rani Marsela; Siahaan, Parlaungan Gabriel; Novridah Reanti Purba; Jane Agustin Sianturi; Ananda Meriah Ate Banurea; Sabar Saur Matua Br Limbong; Asya Junita Rajagukguk; Tasya Maulita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Anonymity comes from the Greek word 'anonymia' which means 'without a name' which means unknown identity information, which can be used to identify objects in the form of humans or objects. This study examines the effect of anonymity on social media on freedom of speech and legal responsibility, with a case study of the "Fufu Fafa" account on Twitter. The research method used is a literature study of the content of the "Fufu Fafa" account. This study aims to understand how anonymity affects user behavior in expressing opinions and how legal responsibility is applied to anonymous accounts. The results of the study show that anonymity can be a double-edged sword in the context of social media. On the one hand, anonymity provides space for individuals to express their opinions without fear, especially on sensitive issues. However, on the other hand, it also encourages irresponsible behavior, such as the spread of false information, hatred, and political slander.